The H α luminosity and stellar mass dependent clustering of star-forming galaxies at 0.7 < z < 1.5 with 3D-HST. Issue 2 (21st July 2022) - Clontz, Callie; Wake, David; Zheng, Zheng
ABSTRACT: We present measurements of the dependence of the clustering amplitude of galaxies on their star formation rate (SFR) and stellar mass ( M * ) at 0.7 < z < 1.5 to assess the extent to which environment affects these properties. While these relations are well determined in the local Universe, they are much more poorly known at earlier times. For this analysis, we make use of the near-infrared HST WFC3 grism spectroscopic data in the five CANDELS fields obtained as part of the 3D- HST survey. We make projected two-point correlation function measurements using ∼6000 galaxies with accurate redshifts, M *, and H α luminosities. We find a strong dependence of clustering amplitude on H α luminosity and thus SFR. However, at fixed M *, the clustering dependence on H α luminosity is largely eliminated. We model the clustering of these galaxies within the halo occupation distribution framework using the conditional luminosity function model and the newly developed conditional stellar mass and H α luminosity distribution model. These show that galaxies with higher SFRs tend to live in higher mass haloes, but this is largely driven by the relationship between SFR and M * . Finally, we show that the small residual correlation between clustering amplitude and H α luminosity at fixed M * is likely being driven by a broadening of the SFR– M * relationship for satellite galaxies.